Consumer preferences for pig welfare – Can the market accommodate more than one level of welfare pork?. (July 2017) - Denver, Sigrid; Sandøe, Peter; Christensen, Tove
Abstract: The purpose of the present paper is to investigate the market potential of pork labelled to indicate medium and high levels of animal welfare. The paper asks, in particular, whether there is a risk that Danish consumers will abandon high level welfare pork if less expensive products with a medium level of animal welfare became available. The study was based on an online questionnaire with a choice experiment involving 396 Danish respondents. The results indicated that the Danish market could accommodate more than one pork product with a welfare label but the price differential separating medium and high level animal welfare pork will have to be quite narrow. In addition, full willingness-to-pay of consumers who want to buy high level welfare pork cannot be relied upon to incentivise new consumers to buy medium welfare pork. Further, raising brand awareness in the shopping situation and improving consumer's understanding of brand attributes for high level welfare brands were found to be vital. Highlights: Many consumers will not pay for improving animal welfare beyond the medium level. Small difference between willingness-to-pay for medium and high level welfare pork Full willingness-to-pay for high level welfare pork cannot be exploited. Increasing brand awareness and consumers' knowledge of brands is vital.